PEMANFAATAN TEKNOLOGI QR CODE UNTUK MENINGKATKAN EFISIENSI PEMESANAN MENU (STUDI KASUS KEDAI MATMOEN, BOYOLALI) - Apriliansyah, Fajri; Hidayat, Ahmad Tri (LPPM UNIVERSITAS BINA INSAN, 2025)
Kedai Matmoen is a culinary business that faces challenges in digitalizing its service process. Currently, the ordering system is still conducted manually, leading to long queues, order recording errors, and reduced operational efficiency. This study aims to develop an interactive web-based ordering system equipped with a QR Code feature, allowing customers to place orders directly from their tables without staff interaction. The research methods include needs analysis, system design using UML, implementation with the Laravel framework, and testing using the black-box method. The results show that the system can reduce customer waiting time, improve order accuracy, and speed up the payment process. The implementation of this system is proven to effectively enhance operational efficiency and improve the customer experience, thereby supporting the digitalization of culinary businesses.